2008
DOI: 10.1108/00242530810853991
|View full text |Cite
|
Sign up to set email alerts
|

Identifying knowledge‐sharing requirements in academic libraries

Abstract: Purpose-The purpose of this paper is to provide an evaluation of the existing state of practice in knowledge sharing in university libraries. Design/methodology/approach-This is survey research which is based on an electronic questionnaire. Findings-Results reveal that the majority of libraries investigated are quite friendly towards knowledge sharing, and the majority of librarians value the importance of knowledge sharing. Results also confirm that the knowledge that they mostly use is mainly intangible know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 14 publications
1
35
0
3
Order By: Relevance
“…However, access to online resources was found to be extensive and comprehensive. Parirokh, Daneshgar & Fattahi (2008), on the basis of a survey in USA, report that how sharing of knowledge through the use of ICT among librarians can improve organizational learning in academic libraries. The findings of the study show that almost all libraries use email and library Website as part of their communication system.…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, access to online resources was found to be extensive and comprehensive. Parirokh, Daneshgar & Fattahi (2008), on the basis of a survey in USA, report that how sharing of knowledge through the use of ICT among librarians can improve organizational learning in academic libraries. The findings of the study show that almost all libraries use email and library Website as part of their communication system.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The results in this study suggested that organizations might invest in promoting inter-unit exchanges and in creating meaningful social nets for more innovative products and better performance. Identifying knowledge sharing requirements in academic libraries has been studied by Parirokh, Daneshgar, and Fattahi (2008) who showed that the majority of libraries that were investigated are quite receptive to knowledge sharing using Web 2.0, and the majority of librarians value the importance of knowledge sharing. It is apparent that there is widespread recognition of the importance of Web 2.0 in knowledge sharing in many organizations and libraries.…”
Section: Social Media and Knowledge Sharingmentioning
confidence: 99%
“…The three major groups of clients of academic libraries-undergraduate students, postgraduate students, and academics-generally have high expectations of the services offered by the library [2,7,8]. This requires librarians to possess an appropriate knowledge of their expectations, sometimes indirectly, through customer feedback, suggestions, casual remarks, news from various faculty meetings, as well as wider commercial and industry knowledge.…”
Section: Customer Knowledge Managementmentioning
confidence: 99%